Application of the Analysis Time Series and Multispectral Images for the Estimation of the Conditions of the Vegetation Covers of the Natural Areas of Southern Spain - Galacho-Jiménez, Federico Benjamín; Quesada Molina, Pablo; Carruana-Herrera, David; Reyes-Corredera, Sergio Jesús (IOAP-MDPI, 2022)
It has been scientifically proven that climate change is a reality. In subarid Mediterranean limates, this fact is observed in the irregular distribution of rainfall, resulting in alternating periods of more or less prolonged drought with episodes of torrential rains concentrated in short periods of time. We have selected 11 natural areas in southern Spain, where we will observe these circumstances and where a series of ecosystems composed of vegetation covers of a high ecological value are found. We start from the question of whether these climatic circumstances are really deteriorating them. For this study, we propose a method that combines three analysis techniques: the design of the time series, the application of vegetation indices, and the use of techniques analysis of changes in land use. From the combination of these techniques in the period from 1997 to 2021, we have observed that there have been a dynamic of changes in land use that has maintained its original characteristics by more than 70%, so it is possible to affirm that the adaptation of ecosystems to climatic conditions has occurred satisfactorily. However, this general statement shows some particularities which are those that we will show in this work.
Keywords: Clima mediterráneo; Subarid Mediterranean climates; Natural areas; Time series; Vegetation indices; Land-use changes; GIS; Remote sensing; MODIS